Manajemen Risiko Keamanan Siber dalam Implementasi Teknologi 5G di Universitas Bhayangkaraya Jakarta Raya - Muhammad Rafi Wijaya; Dimas Setiawan; Malik Alfauziy Hermawan; Nabil Surya Adjhari (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
The 5G arrange innovation offers noteworthy openings to back advanced change over different segments, counting higher instruction. This ponder analyzes cybersecurity chance administration within the usage of 5G innovation on campus, centering on foundation preparation, understudy discernments, and hazard moderation measures. The research was conducted employing a writing survey and a study of understudies from the Staff of Computer Science at Universitas Bhayangkara Jakarta Raya. The discoveries uncover that whereas 5G innovation gives high-speed network and moo inactivity to encourage shrewd campus improvement, critical challenges stay, counting lacking framework, inadequately chance evaluations, and the require for cybersecurity preparing. Most respondents recognize the significance of individual information security and request clear security arrangements and superior security measures. This think about suggests upgrading innovative framework, conducting comprehensive hazard assessments, and powers cybersecurity preparing and mindfulness programs to maximize the benefits of 5G whereas relieving its dangers.